Key Insights on Academic Procrastination for Global Scholars: Wawasan Utama tentang Penundaan Akademik untuk Pelajar Global - RUSYID AFFANDI, GHOZALI (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the relationship between self-efficacy, self-control, and academic procrastination among students in the Faculty of Psychology and Education Sciences at Muhammadiyah University of Sidoarjo (UMSIDA). Utilizing a quantitative correlational design, data from 327 participants were collected using three psychological scales previously tested for reliability and validity on a sample of 30 individuals. Results from multiple linear regression analysis show that both self-efficacy and self-control significantly predict academic procrastination, collectively explaining 45.8% of the variance, with self-efficacy contributing 24% and self-control 21%. Understanding these dynamics has implications for targeted interventions to mitigate academic procrastination and enhance student success and well-being in this academic context. Highlight: Psychological Factors' Impact: Self-efficacy, self-control crucial in academic procrastination. Quantitative Correlational Design: Enhances understanding of variable relationships. Student Support Implications: Inform targeted interventions for student success and well-being. Keyword: self-efficacy, self-control, academic procrastination, psychology education, Muhammadiyah University